Inovasi Guru dalam Pembelajaran Masa Pandemi Covid-19 - Anam, Khoerul; Yahya, M. Slamet (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Learning must be able to run well under any conditions, both normal conditions and emergency conditions. Learning is a need that must be fulfilled properly. Good learning will produce a good generation. Learning in a pandemic period demands creativity and innovation from educators so that learning can run in any condition. In this study, it discusses teacher innovation in learning during the Covid 19 pandemic which demands creativity and innovation because it occurs suddenly as a natural disaster. The results show that The teacher remains enthusiastic in facing learning during the Covid 19 pandemic by trying to continue to carry out learning by innovating in learning methods and using existing learning media, providing materials and a fun evaluation system